Pandemic era and public trust in Southeast Asia: the end or triumph of (post-)modernism? - Zamri, Zahid (Emerald Publishing, 2023)
The debate between modernity and post-modernity has taken the centre stage of philosophical discourse since before the outbreak of the COVID-19 pandemic. Even after the advent of the pandemic, it has yet to be resolved with each camp claiming to be the victor over the other, and therefore sealed a permanent dichotomy between both school of thought. With COVID-19 menacing the world, it is timely to revisit the debate and to come to a conclusion that once and for all will dissolve the fissure between these two dominant theoretical paradigms. It is also hoped that the conclusion made can pave the way for a new theoretical paradigm that is more comprehensive and efficient in facing the post-COVID world. By referring to Southeast Asian communities namely Malaysian, Indonesian, and Singaporean publics, the chapter puts forward the argument that the existing dichotomy between these two theoretical frameworks could no longer sustain its status-quo. This is because the abruption of confusions amongst the public over the issues surrounding the COVID-19 vaccines - and hence on modern science and modernity itself - requires us to stop from rigidly devoting ourselves towards either one of these theoretical paradigms. Based on the case studies, the chapter then suggests for revisions to be made by benefitting from the best of both theoretical paradigms and by omitting those concepts that are no longer effective to be adopted in facing the post-pandemic world.